Effectiveness of Piled Row Breakwater as a Potential Coastal Protection Measure - Bin Zailani , Omar Haziq (Universiti Teknologi PETRONAS, 2018)

(untitled)
Beach erosion is one of the critical issue in Malaysia. Issue that occur in the Pelangi Beach Resort at Langkawi can be determined as disturbed sediments. This can be mean by as the sediments flow from the longshore current deposited and eroded concurrently near the shoreline at a specific area. From the study and research preview, it is found that the pile rows have been installed in the design of ca. 0.6 transmission coefficient at high tide. After a year later, the beach was fully restored more than expected. However, the issue of middle lee side of pile row breakwater is eroded. Extensive research is carried out by conducting experiments leading to discover the optimum wave transformation coefficient. Hydrodynamic characteristics and conditions at the study area are believed to be main reason of extensive erosion. The lack of understanding in coastal development design when implementing some coastal construction project may lead to serious case and imbalance economic. The quantitative effects of pile row breakwater characteristics are still poorly discovered and understood. However, a study to the wave transmission on pile row breakwater investigated in term of theoretically and experimentally studies to understand the hydrodynamic characteristics of the wave transmission either on the lee side or the offshore and thus to determine the optimum transmission coefficient in maintaining the aesthetic values.